Factors Affecting Exclusive Breastfeeding, Using Adaptive LASSO Regression - Najmeh Maharlouei; Amirhosein Pourhaghighi; Hadi Raeisi Shahraki; Dariush Zohoori; Kamran B. Lankarani (International Journal of Community Based Nursing and Midwifery, 2018)
Background: Exclusive breastfeeding (EBF) in the first six months of the life can significantly improve maternal and children health, and it is especially important in low- and middle-income countries. We aimed to determine the factors affecting EBF duration in a sample of Iranian infants. Methods: This prospective study was conducted between April 2012 and October 2014 in Fars, Iran. Women (N=2640), who had given birth to healthy term infants were categorized into EBF versus non-EBF groups. Demographic information from mothers and infants, medical and drug history, and pregnancy related factors were compared between the two groups. Multivariable analysis was performed using Adaptive Lasso regression. P<0.05 was considered significant. Results: The mean duration of EBF was 4.63±1.99 months. There was an inverse association between the mother’s educational level and duration of EBF (P<0.001). Also, we found that mothers who were housewives had a significantly longer duration of EBF (4.68±1.97) compared to mothers with either part-time (4.21±2.01) or full-time jobs (4.02±2.12) (P<0.001). By eliminating the redundant factors, the proposed multivariable model showed the infant’s weight gain during EBF, singleton/multiple pregnancies, maternal perception of quantity of breast milk, post-partum infection, use of pacifier, neonate’s irritability, birth place and mother’s full-time job as the most important factors affecting the duration of EBF. Twin pregnancies, post-partum infection, cesarean section by maternal request, use of a pacifier and irritability in the neonatal period significantly reduced the duration of EBF. Conclusion: Health policy-makers should promote EBF programs among the educated as well as working mothers in order to positively affect the community’s health status.